Probabilistic seismic hazard function based on spatiotemporal earthquake likelihood simulation and Akaike information criterion: The PSHF study around off the west coast of Sumatra Island before large earthquake events - Triyoso, Wahyu (Frontiers in Earth Science, 2023)
The Probabilistic Seismic Hazard Function (PSHF) prior to large earthquake events based on the hypothesis earthquake forecast algorithm using the Akaike Information Criterion (AIC) is done in this study. The motivation for using the AIC is to understand better the reliability model used to construct the PSHF. The PSHF as the function of the b-value is calculated based on a five-year window length with a one-year moving window (instantaneous PSHF) prior to a large earthquake event. The AIC is calculated based on the likelihood of success and failure using shallow earthquake catalog data around the West Coast of Sumatra Island. The probability of occurrence defines the success criteria as more significant than the average probability of greater than or equal to the given magnitude; otherwise defined as failure. And seismic potency has been determined based on the likelihood of an earthquake occurring in several decades or a hundred years. The seismicity rate model is developed based on the integrated data of pre-seismic shallow crustal movement data and the shallow crustal earthquake catalog data. Furthermore, AIC is calculated based on the likelihood of success and failure as a function of b(t). The b(t) is the change of the b-value as a time function estimated based on shallow earthquake data from 1963 to 2016. In addition, the AIC prior to M7.9 of 2000, M8.5 of 2007, and M7.8 of 2010 are assessed. The δAIC is then introduced as a function of – (AICmodel – AICreference) during the observation time. The positive δAIC implies the likelihood of having a large earthquake is more significant and otherwise is smaller. By plotting the time of observation versus δAIC and the PSHF estimated as the function of b(t), we could identify a large positive gradient and increase the PSHF at each certain Probability Exceedance (PE) level prior to the great earthquake event. It consistently happened for the three events that were evaluated. It suggested that the result of this study might be very beneficial for Probabilistic Seismic Hazard Analysis (PSHA) and seismic mitigation realization.